THE EFFECT OF APPLYING GINGER CORRECTOR SOFTWARE AS A CORRECTION TOOL ON THE COMPETENCY OF RECOUNT TEXTS OF THE EIGHTH GRADE STUDENTS OF SMP N 1 UBUD ACADEMIC YEAR 2016/2017 - ., I Made Partha Sarathi; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
kompetensi menulis recount text antara siswa yang menulis dengan dikoreksi menggunakan software Ginger Corrector dan siswa yang menulis dengan dikoreksimenggunakan konvensional feedback. Desain penelitian yang digunakan adalah Quasi-Experimental Design yang disebut Post-test only control group. Populasi dalam penelitian ini adalah siswa kelas delapan SMP Negeri 1 Ubud dengan sample 64 siswa yang dipilih melalui Purposive Sampling. 32 siswa dari kelas VIII A1 sebegai kelas experimen dimana sofware Ginger Corrector diaplikasikan dan 32 siswa dari kelas VIII A2 sebagai kelas control dimana software Ginger Corrector tidak di aplikasikan. Data diambil melalu tes menulis dengan menggunakan rubric penilaian dan dianalisis menggunakan t-test. Hasil dari penelitian menunjukan bahwa terdapat perbedaan yang signifikan dalam nilai menulis recount antara siswa yang diajarkan dengan pengaplikasian Ginger Corrector Software dan siswa yang diajarkan tanpa pengaplikasian software Ginger Corrector sebagai alat pengkoreksi Hal ini dibuktikan oleh hasil statistik deskriptif yang menunjukkan nilai rata-rata dari kelompok eksperimen adalah 79,68 sedangkan nilai rata-rata dari kelompok kontrol adalah 72,50. Hasil uji-t juga menunjukkan bahwa nilai tobs lebih tinggi dari tcv. Nilai tobs adalah 4,430 sedangkan nilai tcv adalah 1,6697. Oleh karena itu, hipotesis nol (Ho) ditolak dan hipotesis alternatif (Ha) diterima.Kata Kunci : kompetensi menulis recount teks, CALL, Software Ginger Corrector. This study aimed to investigate whether or not there is any significant difference in the competency of writing recount texts between the students whose writing which is corrected by Ginger Corrector Software and the students whose writing which is corrected by conventional feedback. This study was quasi-experimental design called posttest-only control group design. The population in this study was eighth grade students of SMP Negeri 1 Ubud with the sample of 64 students selected by using Purpossive Sampling. 32 students of VIII A1 class were assigned as the experimental class which were taught by applying Ginger Corrector Software and 32 students of VIII A2 class as the control class which were taught without applying Ginger Corrector Software. The data were collected by using writing test with scoring rubric and analyzed by using t-test. The result of the research showed that there was a significant difference in writing score of the eighth grade students who were taught by applying Ginger Corrector Software and those who were taught without applying Ginger Corrector Software. It was proven by the result of the descriptive statistics that showed the mean score of the experimental group was 79.68 while the mean score of the control group was 72.50. The result of the t-test also showed that the value of the tobs was higher than the tcv. The value of the tobs was 4.430 while the value of the tcv was 1.6697. Therefore the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) was accepted.keyword : Writing Recount Text Competency, CALL Feedback, Ginger Corrector Software.